2018
DOI: 10.3390/ma11050761
|View full text |Cite
|
Sign up to set email alerts
|

Damage Mechanisms and Mechanical Properties of High-Strength Multiphase Steels

Abstract: The usage of high-strength steels for structural components and reinforcement parts is inevitable for modern car-body manufacture in reaching lightweight design as well as increasing passive safety. Depending on their microstructure these steels show differing damage mechanisms and various mechanical properties which cannot be classified comprehensively via classical uniaxial tensile testing. In this research, damage initiation, evolution and final material failure are characterized for commercially produced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 31 publications
4
39
0
1
Order By: Relevance
“…In addition to the formability evaluation, the difference of elongation between the steel types of local and global formability is typically larger than the values measured in this investigation. Heibel et al reported that there was a difference of 0.04 in ε 3f and 0.10 in true uniform elongation between high-formability dual-phase 800 MPa strength grade and 1000 MPa grade CP steels [35]. As it was observed from the microstructures, all the steels in the present study were more or less dual-phase type steel with varying amounts of retained austenite and hard phases in the ferritic steel matrix.…”
Section: Formabilitysupporting
confidence: 55%
See 3 more Smart Citations
“…In addition to the formability evaluation, the difference of elongation between the steel types of local and global formability is typically larger than the values measured in this investigation. Heibel et al reported that there was a difference of 0.04 in ε 3f and 0.10 in true uniform elongation between high-formability dual-phase 800 MPa strength grade and 1000 MPa grade CP steels [35]. As it was observed from the microstructures, all the steels in the present study were more or less dual-phase type steel with varying amounts of retained austenite and hard phases in the ferritic steel matrix.…”
Section: Formabilitysupporting
confidence: 55%
“…The effect of IBT temperature on the local and global formability was evaluated using true thickness strain at fracture diagram, which was earlier reported to be suitable classification type for high-strength multiphase steels [35]. Figure 11 presents an evaluation of the formability types of the investigated steels, where Steel A and Steel C IBT 450 demonstrated the best balanced local/global formability.…”
Section: Formabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…The hole expandability of AHSSs has been investigated . However, a detailed characterization of the microstructure of the sheet and the changes at the hole edge‐punched has not been deeply realized.…”
Section: Introductionmentioning
confidence: 99%